Effect of Financial Compensation and Flexible Working Arrangement on Performance of Gojeks Driver - Syihabudhin, Syihabudhin; Kinanti, Lulu Sukma (International Journal of Entrepreneurship and Business Management, 2022)
Human Resources (HR) is an important factor in the management of a company, in human resource management the role of workers or employees is an important element in achieving company goals. With the abilities possessed by employees, it will become the existence of the organization in the future, therefore companies are required to create high and quality employee performance. With quality performance the company’s image will be seen as good and more people will be interested in using the services or products issued by the company. This research is the quantitative research using descriptive and explanatory research design. The independent variable in this study is financial compensation (X1) and Flexible Working Arragement (X2), while the dependent variable in this study is Employee Performance (Y), the population taken in this study is the Gojek Driver in Ternate City. The samples taken in this study were 143 respondents, then test the feasibility of the instrument using validity and reliability tests. The analysis technique uses descriptive statistical analysis, classical assumption testm and multiple linear regression analysis. By using an alpha value of 5%, hypothesis testing shows the results that Financial Compensation has a significant effect on employee performance, and Flexible Working Arrangement so has a significant effect on employee performance.